Segmented assimilation, local context and determinants of drug violence in Miami and San Diego: Does ethnicity and immigration matter? - Martínez Junior, R.; Lee, M. T.; Nielsen, A. L.
tbls.
pp. 131-157
Keywords: Inmigrantes; Violencia; Estados Unidos de America; Drogas de Uso Indebido; San Diego; Miami